TcdC Does Not Significantly Repress Toxin Expression in Clostridium difficile 630ΔErm - Bakker, Dennis (Public Library of Science, 2012)
In the past decade, Clostridium difficile has emerged as an important gut pathogen. Symptoms of C. difficile infection range from mild diarrhea to pseudomembranous colitis, sometimes resulting in colectomy or death. The main virulence factors of C. difficile are toxin A and toxin B. Besides the genes encoding these toxins (tcdA and tcdB), the pathogenicity locus (PaLoc) also contains genes encoding a sigma factor (tcdR) and a putative anti-sigma factor (tcdC). The important role of TcdR as a sigma factor for toxin expression is undisputed, whereas the role of TcdC as an anti-sigma factor, inhibiting toxin expression, is currently the subject of debate. To clarify the role of TcdC in toxin expression, we generated an isogenic ClosTron-based mutant of tcdC in Clostridium difficile strain 630Δ Erm (CT::tcdC) and determined the transcription levels of the PaLoc genes and the expression levels of the toxins in the wild type strain and the tcdC mutant strain. We found only minor differences in transcription levels of the PaLoc genes between the wild type and CT::tcdC strains and total toxin levels did not significantly differ either. These results suggest that in C. difficile 630Δerm TcdC is not a major regulator of toxin expression under the conditions tested.